TransCONFIRM: Identification of a genetic signature of response to fulvestrant in advanced hormone receptor positive breast cancer - Jeselsohn, Rinath (Clin Cancer Res, 2016)
PURPOSE: Fulvestrant is an estrogen receptor (ER) antagonist and an approved treatment for metastatic estrogen receptor positive (ER+) breast cancer. With the exception of ER levels, there are no established predictive biomarkers of response to single agent fulvestrant. We attempted to identify a gene signature of response to fulvestrant in advanced breast cancer. EXPERIMENTAL DESIGN: Primary tumor samples from 134 patients enrolled in the phase III CONFIRM study of patients with metastatic ER+ breast cancer comparing treatment with either 250mg or 500mg fulvestrant were collected for genome-wide transcriptomic analysis. Gene expression profiling was performed using Affymetrix microarrays. An exploratory analysis was performed to identify biological pathways and new signatures associated with response to fulvestrant. RESULTS: Pathway analysis demonstrated that increased EGF pathway and FOXA1 transcriptional signaling is associated with decreased response to fulvestrant. Using a multivariate Cox model we identified a novel set of 37 genes whose expression is independently associated with progression free survival (PFS). TFAP2C, a known regulator of ER activity was ranked second in this gene set and high expression was associated with a decreased response to fulvestrant. The negative predictive value of TFAP2C expression at the protein level was confirmed by immunohistochemistry. CONCLUSIONS: We identified biological pathways and a novel gene signature in primary ER+ breast cancers that predicts for response to treatment in the CONFIRM study. These results suggest potential new therapeutic targets and warrant further validation as predictive biomarkers of fulvestrant treatment in metastatic breast cancer.